Netherton Syndrome in a Neonate with Possible Growth Hormone Deficiency and Transient Hyperaldosteronism - Chatziioannidis Ilias; Babatseva Evgenia; Patsatsi Aikaterini; Galli-Tsinopoulou Asimina; Sarri Constantina; Lithoxopoulou Maria; Mitsiakos George; Karagianni Paraskevi; Tsakalidis Christos; Mamuris Zissis; Nikolaidis Nikolaos (Case Reports in Pediatrics)
Netherton syndrome, a rare autosomal recessive genetic disorder, is classified as an ichthyosiform syndrome. In this report we present the case of a neonate with erythroderma shortly after birth, accompanied by severe hypernatremia, recurrent infections, transient hyperaldosteronism, and signs of growth hormone (GH) deficiency. DNA molecular analysis in the SPINK5 gene revealed heterozygosity in our index patient for 238insG and 2468delA frameshift mutations in exons 4 and 26, respectively, in the maternal allele and 1431-12G>A splice-site mutation in intron 15 in the paternal allele as well as the missense variation E420K in homozygous state. Combination of the identified mutations along with transient hyperaldosteronism and possible GH deficiency have not been described before. Accordingly, the importance of early multidisciplinary approach is highlighted, in order to reach accurate diagnosis, initiate prompt treatment, and ensure survival with fewer disease complications.